A visualized study of enhanced steam condensation heat transfer on a honeycomb-like microporous superhydrophobic surface in the presence of a non-condensable gas. (April 2020) - Zhang, Tian-Yu; Mou, Lin-Wei; Zhang, Jia-Yi; Fan, Li-Wu; Li, Jia-Qi
Highlights: Steam condensation was investigated in the presence of a non-condensable gas (NCG). Stable droplet jumping mode was realized on a microporous superhydrophobic surface. Different droplet behaviors were observed at various NCG contents and subcoolings. Mechanisms for enhancement of condensation heat transfer with NCG were elucidated. This work sheds light on the strategy for condensation enhancement in case of NCG. Abstract: Steam condensation is a ubiquitous phenomenon of phase change that can be encountered in various industrial applications. In practice, the presence of non-condensable gases (NCG) is often inevitable, which can severely deteriorate condensation heat transfer by accumulating in the vicinity of the condensing surface as an additional thermal resistance. In this work, steam condensation heat transfer on a honeycomb-like microporous superhydrophobic surface, which has already been shown to lead to stable coalescence-induced droplet jumping with high heat flux, was studied with NCG concentrations up to 28%. The superhydrophobic surface, having a nominal pore diameter of 20 μm, was prepared by a rapid, cost-effective and highly scalable electrodeposition method over the outer surface of thin copper tubes. Condensation experiments were conducted in a visualized vacuum chamber maintaining at a constant pressure of 9.5 kPa. Significant enhancements of condensation heat transfer at the various NCG concentrations were exhibited on such superhydrophobic surface over a wide range of subcooling up to 35 K, due to the successful realization of droplet jumping in spite of the presence of NCG. The adsorption of NCG into the micropores was elucidated to be a partial reason for prohibition of condensate flooding at relatively high degrees of subcooling.